1891 Wis. Sess. Laws 186, ch. 40, § 28, pt. 60 - (:unkn) unknown (My University, 1891)
Authorized the city to regulate or prohibit the concealed carry of any pistol, revolver, sling shot, cross knuckles, knuckles made of lead, brass, or other metal, or Bowie knife, dirk knife, dirk, or dagger, or any other dangerous or deadly weapons.
Keywords: CARRY - CONCEALED